(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2022)
The agricultural sector has contributed to environmental pollution, such as water and air pollution caused by the fertiliser used in agriculture is lost into the river or to the air through the leaching process. Studies in the literature have shown that slow-release fertiliser (SRF) application could help overcome the leaching problem as it releases its nutrients slower. In other words, SRF is expected to help maintain the nutrients’ availability in the soil for a more extended period and extends the plants’ nutrient uptake efficiency. The experimental design for this study was completely randomized design with 4 different treatments T0 (control) was treatment without fertilizer application; T1 (SRF applied once in a month); T2 (CF applied once in a month); T3 (SRF applied twice in a month) and T4 (CF applied twice in a month). This study aimed to compare the plant growth rate (plant height, number of leaves and plant yield) of using SRF and conventional fertiliser (CF) on okra (Abelmoschus esculentus L. Moench). This study shows that SRF does show a good option to promote the growth development of okra (plant height, number of leaves and chlorophyl content) but not on the yield.